2018
DOI: 10.1093/ajcn/nqy050
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents at high risk of obesity show greater striatal response to increased sugar content in milkshakes

Abstract: Collectively, the data presented here suggest that parental weight status is associated with greater striatal, gustatory, and somatosensory responses to palatable foods-in particular, high-sugar foods-in their adolescent offspring, which theoretically contributes to an increased risk of future overeating. This trial was registered at www.clinicaltrials.gov as NCT01949636.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 44 publications
(50 reference statements)
2
32
0
1
Order By: Relevance
“…Additionally, greater response in caudate was observed, similar to other studies of palatable taste [86][87][88]. These results add further evidence to support brain response to palatable taste in the describe regions.…”
Section: Brain Response and Network Organization During Appetitive Pstsupporting
confidence: 89%
“…Additionally, greater response in caudate was observed, similar to other studies of palatable taste [86][87][88]. These results add further evidence to support brain response to palatable taste in the describe regions.…”
Section: Brain Response and Network Organization During Appetitive Pstsupporting
confidence: 89%
“…On the other hand, one study found that elevated responsivity of regions implicated in reward processing predicted future weight gain, though that study used a very small sample (n = 16; Geha et al, 2013). Interestingly, two studies have found that healthy weight adolescents at high risk for future weight gain by virtue of parental obesity showed elevated reward region response to receipt of high-calorie beverages (Shearrer, Stice, & Burger, 2018; Stice et al, 2011). Collectively, the pattern of findings provide little reliable support for the thesis that elevated responsivity of regions implicated in reward to high-calorie food receipt increases risk for future weight gain (Davis et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A food picture paradigm was adopted to test neural responses to imagined consumption in response to pictures of appetizing foods, unappetizing foods, and glasses of water. Food pictures were individualized based on the participants’ previous appetizing ratings [see earlier papers for details on this paradigm (Shearrer et al., 2018; Stice and Yokum, 2018)]. During the task, each picture was presented for five seconds and participants were instructed to imagine tasting and eating the pictured food.…”
Section: Methodsmentioning
confidence: 99%
“…Each image type was presented for 32 trials. This paradigm elicits robust food reward-related neural response (Shearrer et al., 2018; Stice and Yokum, 2018).…”
Section: Methodsmentioning
confidence: 99%